The Civil Defense Volunteers’ Participation on the Prevention and Mitigation Mission - Lapsan, Kiattisak (Journal for Developing the Social and Community, 2018)
Now a lot of disasters occur and more intensified which make a damage to public life and property envelopes. The Civil Defense Volunteers (AP) is people who play an important role on management of disasters in self-sufficiency communities. This is the preparation for junction to reduce the loss of life and property of victims in the first place before external agencies come to help. The Civil Defense Volunteers (AP) was in the prevention and mitigation of public disaster as a blessing, it is responsible for preventing and mitigating the disaster in field of communication to get information about preventive and relief working. Looking for hear the disaster from broadcasting community radio stations public radio and local newspapers. Training involved in disseminating knowledge about disaster relief and rescue to members of volunteer rescue units. Attend training or demonstration on rescue and disaster relief, and support or assist staff in training or demonstration. In the case of disaster relief and disaster prevention, such as rescue of flood victims, fire and windstorm, and participation in performing duties with government agencies in social services, participation in social welfare activities during major festivals such as New Year, Songkran Festival etc. Therefore, people who was the civil defense volunteers can cooperate with government agencies to help victims of civil unrest as a network to government in prevention and mitigation of public envelope.